Price Dynamics and Market Integration of Red Chili Between Farmers and Consumers in Banyumas Regency, Indonesia - Putri, Dindy Darmawati; Karim, Akhmad Rizqul; Wijayanti, Irene Kartika Eka; Zulkfli, Lutfi; Prasetyo, Kunandar (Universitas Panji Sakti, 2025)
Chili is one of the food commodities that has a fluctuating price. The instability of this price movement makes red chili a cause of price inflation in Banyumas Regency. This study aims to find out the marketing channels, price behavior, and market integration of red chili commodities in Banyumas Regency. The types and sources of data in this study are primary and secondary data. Primary data were obtained based on interviews with traders. Secondary data in the form of red chili prices that apply at the farmer and consumer levels in Banyumas Regency in the period 2019 to 2023. Red chili price data at the farmer level comes from the Department of Agriculture and Food Security of Banyumas Regency. Red chili price data at the consumer level comes from the Department of Industry and Trade of Banyumas Regency. The analysis method in this study is a descriptive quantitative method. Data analysis uses descriptive analysis, coefficient of variation, and Vector Error Correction Model (VECM). The results of the study indicate that the behavior of red chili prices based on the KV values obtained indicates highly fluctuating and unstable behavior. The average KV value at the farmer level, which is 43%, tends to be greater than the consumer level, which is 41%. This shows that the price of red chili at the farmer level is more fluctuating than at the consumer level. The red chili market at the farmer and consumer levels in Banyumas Regency is integrated both in the long term and the short term. There is no causal relationship between the producer and consumer markets in the marketing of red chili in Banyumas Regency.